Comparative impacts of fragmentation on birds in two bioregions in a biodiversity hotspot, the Cape Floristic Region - Kieck, Marius Burger (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MScConsEcol (Conservation Ecology and Entomology))--University of Stellenbosch, 2009.